Cuscuta chinensis Lam. Protects Against Light-Induced Retinal Degeneration: Therapeutic Implications for Photoreceptor Degenerative Disorders - Wu, Hanhan; Zhu, Beijing; Li, Daijin; Xu, Jing; Chang, Jie; Du, Xiaoye; Cui, Jingang; Zhang, Ning; Zhang, Teng; Chen, Yu (Frontiers in Pharmacology, 2022)
Cuscuta chinensis Lam. (CCL) is a medicinal herb widely used in traditional Chinese medicine for the treatment of ophthalmic diseases, including age-dependent vision-threatening retinal degenerative disorders that involve irreversible loss of the first-order retinal neurons, photoreceptors. However, evidence is lacking if CCL is pharmacologically active at protecting against loss of photoreceptors and photoreceptor degeneration-associated retinal structural and functional impairment. The current study thus evaluates the potential photoreceptor protective effects of CCL to better support its clinical applications in the prevention and treatment of photoreceptor degenerative diseases. Non-invasive full-retinal optical coherence tomography, electroretinography, histological examination, immunohistochemistry and real-time qPCR analysis were performed to assess the retinal protective effects of CCL in light-exposed BALB/c mice characterized by photooxidative stress-mediated photoreceptor loss and associated retinal morphological and functional impairment. The results showed that CCL treatment protected against light-induced degeneration of the photoreceptor structure and deterioration of the retinal function. Furthermore, CCL treatment increased the retinal expression of rhodopsin, S-opsin and M-opsin, supporting the protective effects of CCL in both rod and cone photoreceptors. CCL treatment suppressed photoreceptor cell death in the light-exposed retinas. The morphological integrity of the second-order retinal neurons was also preserved as a result of CCL treatment. In addition, CCL treatment attenuated light-induced reactive müller gliosis, microglial activation and inflammation in the retina. In conclusion, the current work demonstrates for the first time that CCL protects against photooxidative stress-mediated degeneration of photoreceptors and associated disturbance of structural, functional and immune homeostasis of the retina. The findings here thus provide novel experimental evidence supporting the clinical application of CCL in the prevention and treatment photoreceptor degenerative diseases.